2020
DOI: 10.1161/strokeaha.119.026845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clopidogrel-Aspirin Therapy for Stroke Does Not Exist in C YP2C19 Loss-of-Function Allele Noncarriers With Overweight/Obesity

Abstract: Background and Purpose— The role of dual-antiplatelet therapy with clopidogrel plus aspirin has been demonstrated to substantially decrease the risk of recurrent stroke among patients with minor stroke and transient ischemic attack. We aimed to determine whether the efficacy of clopidogrel-aspirin therapy among patients with minor stroke / transient ischemic attack was influenced by the stratification of CYP2C19 genotype and body mass index (BMI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In our study, BMI was associated with a significant CYP2C19 activity reduction, which is supported by the literature 35,36 . In fact, the rate of high on‐treatment platelet reactivity to clopidogrel was significantly associated with higher BMI as well as CYP2C19 loss‐of‐function alleles (LoFAs) carrier (*2 or *3) 35 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, BMI was associated with a significant CYP2C19 activity reduction, which is supported by the literature 35,36 . In fact, the rate of high on‐treatment platelet reactivity to clopidogrel was significantly associated with higher BMI as well as CYP2C19 loss‐of‐function alleles (LoFAs) carrier (*2 or *3) 35 .…”
Section: Discussionsupporting
confidence: 87%
“…5 In our study, BMI was associated with a significant CYP2C19 activity reduction, which is supported by the literature. 35,36 In fact, the rate of high on-treatment platelet reactivity to clopidogrel was significantly associated with higher BMI as well as CYP2C19 loss-of-function alleles (LoFAs) carrier (*2 or *3). 35 In LoFA noncarriers with overweight/obesity, clopidogrel-aspirin therapy was not efficient in reducing the risk of stroke recurrence as compared with LoFA noncarriers with low/normal weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, BMI significantly influences the association between clopidogrel therapy and the CYP2C19 genotype, and extreme BMI (low and high) predicts the escalation of the bleeding risk (30). However, BMI does not accurately describe body fat accumulation, and surrogate markers of abdominal obesity, such as WHR or waistline circumference, might be more important predictors for unfavorable outcomes in patients with recent AMI with antithrombotic-related CSDH.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that patients with minor stroke/transient ischemic attack with overweight/obesity did not benefit from clopidogrel therapy, and that body mass index (BMI) was a major independent predictor of an insufficient antiplatelet response to clopidogrel ( 29 ). Higher BMI was directly related to hypercholesterol and TGs, and inversely related to HDL cholesterol ( 30 ).…”
Section: Discussionmentioning
confidence: 99%